Model‐based design of an autonomous function for responsive satellite operations. Issue 1 (July 2017) - Obata, Toshihiro; Nakasuka, Shinichi; Shirasaka, Seiko
Abstract: PROMPT (PRompt Observation Methodology with intelligent Pointing and Testing) is a concept for the responsive observation method used by a satellite with an autonomous function on board. This paper shows its concept of how to shorten the timeline to observation of days to a month that normal satellites take after their launch. It also shows a model‐based design of an autonomous function that enables a robust satellite behavior against on‐orbit uncertainties.